2016
DOI: 10.1038/srep26981
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted surgery versus open surgery in the treatment of rectal cancer: the current evidence

Abstract: The aim of this meta-analysis was to comprehensively compare the safety and efficacy of robotic-assisted rectal cancer surgery (RRCS) and open rectal cancer surgery (ORCS). Electronic database (PubMed, EMBASE, Web of Knowledge, and the Cochrane Library) searches were conducted for all relevant studies that compared the short-term and long-term outcomes between RRCS and ORCS. Odds ratios (ORs), mean differences, and hazard ratios were calculated. Seven studies involving 1074 patients with rectal cancer were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…Several studies have demonstrated that RALS is a safe and feasible approach in various colorectal procedures; however, robust clinical evidence supporting the benefit of robotic‐assisted surgery for rectal cancer remains limited. The results from recent RCTs and meta‐analyses of RALS vs CLS or OS for rectal cancer are summarized in Table . Several recent meta‐analyses have shown a significant difference in the outcomes between RALS and CLS for rectal cancer, including the rates of conversion to OS and positive CRM.…”
Section: Short‐term Outcomesmentioning
confidence: 99%
“…Several studies have demonstrated that RALS is a safe and feasible approach in various colorectal procedures; however, robust clinical evidence supporting the benefit of robotic‐assisted surgery for rectal cancer remains limited. The results from recent RCTs and meta‐analyses of RALS vs CLS or OS for rectal cancer are summarized in Table . Several recent meta‐analyses have shown a significant difference in the outcomes between RALS and CLS for rectal cancer, including the rates of conversion to OS and positive CRM.…”
Section: Short‐term Outcomesmentioning
confidence: 99%
“…Lee et al [67] showed no differences in operative time between robotic and transanal-TME [67] . Other studies reported less blood loss for robotic TME, compared with the open and laparoscopic approaches [68,69] . Intraoperative complications were found similar for robotic surgery when compared with the open and laparoscopic approaches [26,66] .…”
Section: Intraoperative Outcomesmentioning
confidence: 98%
“…Anastomotic leak rate was not significantly different for robotics compared with open and laparoscopic operations [28,69] . Laparoscopic, transanal, and robotic TME also showed similar leak and reoperation rates [67,70] .…”
Section: Postoperative Outcomesmentioning
confidence: 99%
“…A systematic review and metaanalysis of seven studies with 1074 patients compared the safety and efficacy of robot-assisted versus open surgery in rectal cancer. 27 Robotic-assisted surgery was associated with decreased intraoperative blood loss (EBL), shorter length of stay, and shorter time to flatus, but longer operation times. There were no differences in complications, distal resection margin, or disease-free survival between the two groups.…”
Section: Robotic Anastomosis After Right Colectomymentioning
confidence: 99%